2007
DOI: 10.1016/j.cmet.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A Central Thermogenic-like Mechanism in Feeding Regulation: An Interplay between Arcuate Nucleus T3 and UCP2

Abstract: The active thyroid hormone, triiodothyronine (T3), regulates mitochondrial uncoupling protein activity and related thermogenesis in peripheral tissues. Type 2 deiodinase (DII), an enzyme that catalyzes active thyroid hormone production, and mitochondrial uncoupling protein 2 (UCP2) are also present in the hypothalamic arcuate nucleus, where their interaction and physiological significance have not been explored. Here, we report that DII-producing glial cells are in direct apposition to neurons coexpressing neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
229
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(245 citation statements)
references
References 64 publications
9
229
1
6
Order By: Relevance
“…5 B and C). Previous work had suggested that the rise in NPY and AgRP resulted from a local increase in T3 production because of increased expression of deiodinase 2 (DIO2) (23). Fasting-induced up-regulation of DIO2 also is aberrant in the MC3-R −/− mouse (Fig.…”
Section: Mc3-r −/− Mice Exhibit Elevated Basal Corticosterone and Defmentioning
confidence: 81%
See 2 more Smart Citations
“…5 B and C). Previous work had suggested that the rise in NPY and AgRP resulted from a local increase in T3 production because of increased expression of deiodinase 2 (DIO2) (23). Fasting-induced up-regulation of DIO2 also is aberrant in the MC3-R −/− mouse (Fig.…”
Section: Mc3-r −/− Mice Exhibit Elevated Basal Corticosterone and Defmentioning
confidence: 81%
“…Fasting-induced refeeding is also impaired in the NPY −/− , DIO2 −/− , and uncoupling protein 2 (UCP2) −/− mice (23,50,51). Interestingly, a single pathway has been proposed to be responsible for the altered fasting-induced refeeding in the NPY-, DIO2-, and UCP2-knockout models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormone exhibits a number of effects that are mediated directly at the medial basal hypothalamus. An example is the increase in food intake that rapidly follows administration of T 3 directly into the ventromedial nucleus (514)(515)(516). A related approach is to implant T 3 crystals stereotaxically into discrete hypothalamic areas.…”
Section: And Recommendation 44amentioning
confidence: 99%
“…One of these mitochondrial proteins, UCP2, is found in the CNS and has been implicated in various neuronal mechanisms (Andrews et al, 2005a). We and others have shown that UCP2 is involved in neuroprotection in mice models of Parkinson's disease (Andrews et al, 2005b;Conti et al, 2005), epilepsy , and stroke (Mattiasson et al, 2003) as well as in normal functioning of the nigrostriatal dopamine system (Andrews et al, 2006) and the arcuate nucleus melanocortin system (Coppola et al, 2007;Andrews et al, 2008). Induction of UCP2 expression in the brain by cellular stress increases the overall production of ATP, perhaps as a result of stimulation of mitochondrial proliferation, while decreasing superoxide production and associated damage Diano et al, 2003, Andrews et al, 2005b.…”
Section: Introductionmentioning
confidence: 99%